La responsiveness dei sistemi sanitari: un'analisi empirica sull'assistenza ospedaliera nel Servizio Sanitario Regionale dell'Emilia Romagna - Silvana Robone; Gianluca Fiorentini; M. Augusta Nicoli; Rodella Stefania (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
– The release of the World Health Report 2000 has brought to the fore the concept of responsiveness as an indicator of health system performance. Responsiveness relates to a system's ability to respond to the legitimate expectations of potential users about non-health enhancing aspects of care (Valentine et al. 2003). A few studies have investigated how standard socio-demographic characteristics (such as income or education) have an influence on the evaluation of responsiveness by health care users (Puentes Rosas et al. 2006, Sirven et al. 2012, Rice et al. 2012). However, we are not aware of any study investigating the relationship between the frequency with which patients use health services and their evaluation of responsiveness. This paper narrows this gap by using data regarding a sample of patients hospitalized in 9 hospitals of Emilia Romagna, a Region of Italy. The data have been collected by the Agency for Health Care and Social Services of Emilia Romagna between January 2010 and December 2012. We investigate a representative sample of about 2500 in-patients, who have been asked to evaluate 29 different aspect of quality of care which refer to 6 domains of health system responsiveness (communication, social support, privacy, dignity, waiting times and quality of facilities). We make use of this structure of the data by adopting a panel data regression model. The adoption of a panel model helps in controlling for individual heterogeneity, which otherwise could bias our results. Given that responsiveness is evaluated on an ordinal and categorical scale (going from "very dissatisfied" to "very satisfied") we estimate a panel ordered logit model. Our results suggest that if patients have already been hospitalized in the same ward over the last 5 years they evaluate responsiveness more positively compared to patients who have never been hospitalized before. However, this effect is statistically significant only if patients have been hospitalized in the last 6 months. More generally, the use of a proper methodology to investigate responsiveness at hospital level can allow a better identification of area of intervention for investments in staff training; moreover, it can allow to modify hospital characteristics which have a negative impact on patients' reporting of responsiveness.
Keywords: I11; I19; C50; 330